Singaporean teaching methodology: potential for use in the Kyrgyz education system (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the Singapore teaching model as an effective strategy for improving the quality of education and enhancing students’ functional literacy in Kyrgyzstan. Drawing on the results of international assessments such as PISA and TIMSS, the study substantiates the relevance of applying the CPA (Concrete–Pictorial–Abstract) approach and bar modeling. The initial implementation outcomes in 2024–2025 reveal several advantages, while also identifying systemic challenges and strategic measures required for the successful and long-term adaptation of this methodology to the national educational context.
Keywords: Singapore method, CPA, bar model, PISA, TIMSS, STEAM, Kyrgyzstan, reform